Nanocomposite materials for fused filament fabrication. (2021) - Patel, Abhishek; Taufik, Mohammad
Abstract: Fused filament fabrication (FFF) is an innovative technology in which parts are manufactured by depositing layers of materials one above the other. FFF involves the manufacturing of components from bottom to top by adding layers of material one at a time. FFF technology is only a few decades old. FFF is the most extensively used 3D printing process because of its unique combination of simplicity, reduced cost, and speed. Nowadays, FFF becomes commercial technology due to the adaptation of diverse materials in various industrial applications. As, the different industrial application requires FFF material of prescribed specifications including physical, thermal, electrical, and mechanical properties. Mainly polymers were used and then composites were developed and used as they offer better material properties of processed parts. In this direction, advancement in nanotechnology has opened doors for the development of improved FFF material which offers better material properties comparing to conventional feed material available in the market for different industrial applications. Printable polymer composites, mainly polymer nanocomposites, are quickly growing the FFF materials range, allowing for the manufacturing of multifunctional components with intricate structures. To test the feasibility of nanocomposites to be used in FFF, several attempts have been made by researchers, and encouraging results were obtained. However, there is limited literature work reported to summarise the improvement in properties of composite material and their applications in FFF. This paper offers a comprehensive review of the literature available on composites for FFF and how the inclusion of nanofiller material in thermoplastic polymer alters the material properties of manufactured components. This paper also reviews the effect on material properties for polymers by adding more than one filler material. Finally, changes in properties are tabulated for different polymers and nanofillers. Besides, nanoparticle agglomeration, selecting the correct loading ratio, optimizing process parameters, and achieving exfoliation are addressed.